India : Is the Rising Tide Lifting All Boats? - Topalova, Petia (IMF Working Papers; Working Paper ;, 2008)
While many have celebrated India's accelerating economic growth, some have expressed concern about the distributional impacts of the growth process. Cognizant of the vulnerability of its large population below poverty, India's authorities have made faster and more inclusive economic growth the primary goal of their development strategy. This paper aims to document how the benefits of economic expansion were shared across the income distribution over the last two decades using disaggregate household level data. Experiences across Indian states suggest an important role for economic policy in shaping the inclusiveness of growth. States with higher financial development, more flexible labor markets, and higher average education experienced greater relative gains for the poor. Improving infrastructure may also lead to a growth process that is more inclusive of the poor.